2001
DOI: 10.1103/physrevd.63.065002
|View full text |Cite
|
Sign up to set email alerts
|

Radion dynamics and electroweak physics

Abstract: The dynamics of a stabilized radion in the Randall-Sundrum model with two branes is investigated, and the effects of the radion on electroweak precision observables are evaluated. The radius is assumed to be stabilized using a bulk scalar field as suggested by Goldberger and Wise. First the mass and the wave function of the radion is determined including the back reaction of the bulk stabilization field on the metric, giving a typical radion mass of the order of the weak scale. This is demonstrated by a pertur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

46
760
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 428 publications
(808 citation statements)
references
References 117 publications
46
760
0
2
Order By: Relevance
“…A simple example is that of a singlet scalar, φ, which has been extensively discussed (see e.g., [5][6][7][8][9][10][11][12]). To allow for production from gluon fusion at the LHC the singlet must couple to extra vectorlike colored matter, yφΨΨ, necessitating the introduction of many new degrees of freedom.…”
Section: Higgs Signals From Singletsmentioning
confidence: 99%
“…A simple example is that of a singlet scalar, φ, which has been extensively discussed (see e.g., [5][6][7][8][9][10][11][12]). To allow for production from gluon fusion at the LHC the singlet must couple to extra vectorlike colored matter, yφΨΨ, necessitating the introduction of many new degrees of freedom.…”
Section: Higgs Signals From Singletsmentioning
confidence: 99%
“…Goldberger and Wise showed that a bulk scalar field propagating in the background geometry, Eq. (1), can generate a potential that can stabilize L. [24] In order to reproduce the value kL ≃ 35, the radion should have a lighter mass than that of the Kaluza-Klein modes of all bulk fields [25]. Thus, the detection of the radion may well be expected as the first signal to indicate that the RS model is truly realized in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Radion stabilization using the GoldbergerWise mechanism [43] can be understood as a stable minimum for the dilaton potential being generated by effects which explicitly violate conformal symmetry [27]. Several authors have studied the couplings of the radion in Randall-Sundrum models, both in the case when the SM fields are localized to a brane [43][44][45][46] and in the case when they are in the bulk [47,48]. We find excellent * A closely related result has been obtained in the context of walking gauge theories using current algebraic methods [31].…”
Section: Introductionmentioning
confidence: 99%